Post-flambage unilatéral des films minces sur substrat: Transitions entre équilibres - Parry, Guillaume; Colin, Jérôme; Coupeau, Christophe; Cimetière, Alain (European Journal of Computational Mechanics, 2007)
Various buckling equilibria can be observed on the delaminated areas of thin films. These equilibria are usually under advanced post-buckling. Results of the finite element analysis for the post-buckling equilibria of a thin film delaminated along a rectangular strip are discussed in this paper. Those results are compared with experimental observations performed with the help of an in-situ atomic force microscope coupled to a compression device which allows to vary the biaxial stress state in the film. The transitions from straightsided blisters to bubbles or telephone cord blisters are characterized. Both sub-critical and super-critical transitions are highlighted. A mapping of the various stable post-critical equilibria is given.